Development of construction waste management framework for refurbishment projects - Norfadhillah Yahaya,; Azlan Shah Ali, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The high demand of building refurbishment creates an increase in construction waste. Construction waste has been associated with a negative impact on the performance of refurbishment projects such as delay and over budget. Therefore, construction wastes in refurbishment projects have been identified as an important issue to improve the waste management of the refurbished building. The main objective of this paper is to establish a relationship between the causes of construction waste towards cost and time overruns. This study further analysed the mitigation measures that can minimise construction waste. The primary data were obtained using questionnaire surveys that were distributed among quantity surveyors, in Peninsular Malaysia, who oversee refurbishment projects. Through an extensive literature review, both qualitative and quantitative data were employed. A set of questionnaire surveys was initially conducted for sixty-five (65) projects, followed by semi-structured interviews for five (5) interviewees, so as to validate the critical causing factor and to establish a correlation between the factors. The obtained data were then analysed using the ‘Statistical Package for Social Science’ (SPSS). The inferential analysis method through Spearman correlation test was applied to test all correlations in this study, while the descriptive analysis was used to evaluate the demographic of the respondents. The results indicated a significant relationship between the causes of material waste and the performance of refurbishment projects. The analysis revealed that design changes, poor storage and improper packaging are the most prominent factors that cause material waste. These causes demonstrate a significant correlation with the performance of refurbishment projects. On the other hand, proper storage, the handling of materials on site and good construction management were identified as not significantly correlated, however, they possess high potential for mitigation measures. Therefore, an integrated refurbishment waste framework was established, which involved the causes-effect correlation, as well as, the mitigation measures for solving it.